EDUKASI PENANGANAN PENCEGAHAN NYERI LUTUT DENGAN LATIHAN AKTIF DI DESA PADANG TEPONG KECAMATAN ULU MUSI KABUPATEN EMPAT LAWANG - Juliastuti Juliastuti Juliastuti (Khidmah, 2021)
Osteoarthritis is a non-inflamatory degenerative joint disorder that occurs in moving joints, characterized by deteriorating joint cartilage and heave in sight of osteophyte. Some of the symptoms of knee pain, credulity, and morning stiffness are a sign of osteoarthritis in the knee. The result of this activity was 23 people in padang tepong who had complaints of knee pain as one of the symptoms of osteoarthritis of the knee. Keywords: Physiotherapy, Active Exercise, Osteoarthritis Genu